Motivasi dan persepsi wisatawan terhadap potensi wisata di kepulauan mentawai - Pristiwasa, I Wayan Thariqy Kawakibi (Jurnal Kepariwisataan dan Hospitalitas; Vol 1 No 2 (2017): Vol.1,No.2,2017, 2017)
This study aims to find the components of the perception of tourists to the perception of tourism in the Mentawai islands as a tourist destination that is a strategic plan that can be developed for the development of tourism and improve the welfare of the community. This research uses descriptive qualitative research method with reference to the concept of tourism development. Population in this research is in the form of social situation with the participant that is in it that is Government and stakeholder of tourism, tourist and community. Intruments in this study are observation, and interviews using model coding, interpretation and congrulation.      The results of this study show that the perception of tourists can bring positive and negative impacts. Positive impacts can be seen in the improvement of the economy of the community around the tourist area and also contributes to the acquisition of local revenue. While negative impacts include: air pollution, water pollution, garbage, destruction of historical sites, and land use issues.   Keywords: Tourism, Perception of tourists, Government, stakeholder, Community